TCF7 is not essential for glucose homeostasis in mice - Kiran Deep Kaur; Chi Kin Wong; Laurie L. Baggio; Jacqueline L. Beaudry; Shai Fuchs; Brandon L. Panaro; Dianne Matthews; Xiemin Cao; Daniel J. Drucker (Elsevier, 2021)
Objective: Glucose-dependent insulinotropic polypeptide (GIP) and Glucagon-like peptide-1 (GLP-1) are incretin hormones that exert overlapping yet distinct actions on islet β-cells. We recently observed that GIP, but not GLP-1, upregulated islet expression of Transcription Factor 7 (TCF7), a gene expressed in immune cells and associated with the risk of developing type 1 diabetes. TCF7 has also been associated with glucose homeostasis control in the liver. Herein we studied the relative metabolic importance of TCF7 expression in hepatocytes vs. islet β-cells in mice. Methods: Tcf7 expression was selectively inactivated in adult mouse hepatocytes using adenoviral Cre expression and targeted in β-cells using two different lines of insulin promoter-Cre mice. Glucose homeostasis, plasma insulin and triglyceride responses, islet histology, hepatic and islet gene expression, and body weight gain were evaluated in mice fed regular chow or high fat diets. Tcf7 expression within pancreatic islets and immune cells was evaluated using published single cell RNA-seq (scRNA-seq) data, and in islet RNA from immunodeficient Rag2−/−Il2rg−/− mice. Results: Reduction of hepatocyte Tcf7 expression did not impair glucose homeostasis, lipid tolerance or hepatic gene expression profiles linked to control of metabolic or immune pathways. Similarly, oral and intraperitoneal glucose tolerance, plasma insulin responses, islet histology, body weight gain, and insulin tolerance were not different in mice with targeted recombination of Tcf7 in insulin-positive β-cells. Surprisingly, islet Tcf7 mRNA transcripts were not reduced in total islet RNA containing endocrine and associated non-endocrine cell types from Tcf7βcell−/− mice, despite Cre-mediated recombination of islet genomic DNA. Furthermore, glucose tolerance was normal in whole body Tcf7−/− mice. Analysis of scRNA-seq datasets localized pancreatic Tcf7 expression to islet progenitors during development, and immune cells, but not within differentiated islet β-cells or endocrine lineages within mature islets. Moreover, the expression of Tcf7 was extremely low in islet RNA from Rag2−/−Il2rg−/− mice and, consistent with expression within immune cells, Tcf7 was highly correlated with levels of Cd3g mRNA transcripts in RNA from wild type mouse islets. Conclusions: These findings demonstrate that Tcf7 expression is not a critical determinant of glucose homeostasis in mice. Moreover, the detection of Tcf7 expression within islet mRNA is attributable to the expression of Tcf7 RNA in islet-associated murine immune cells, and not in islet β-cells.